CATTLE (CAncer treatment treasury with linked evidence): An integrated knowledge base for personalized oncology research and practice. (13th March 2017) - Soysal, E; Lee, H‐J; Zhang, Y; Huang, L‐C; Chen, X; Wei, Q; Zheng, W; Chang, JT; Cohen, T; Sun, J; Xu, H
Abstract : Despite the existence of various databases cataloging cancer drugs, there is an emerging need to support the development and application of personalized therapies, where an integrated understanding of the clinical factors and drug mechanism of action and its gene targets is necessary. We have developed CATTLE (CAncer Treatment Treasury with Linked Evidence), a comprehensive cancer drug knowledge base providing information across the complete spectrum of the drug life cycle. The CATTLE system collects relevant data from 22 heterogeneous databases, integrates them into a unified model centralized on drugs, and presents comprehensive drug information via an interactive web portal with a download function. A total of 2, 323 unique cancer drugs are currently linked to rich information from these databases in CATTLE. Through two use cases, we demonstrate that CATTLE can be used in supporting both research and practice in personalized oncology.